Acetalization of glycerol using mesoporous MoO3/SiO2 solid acid catalyst - Shubhangi B. Umbarkar; Kotbagi, Trupti V.; Biradar, Ankush V.; Pasricha, Renu; Chanale, Jyoti; Dongare, Mohan K.; Mamede, Anne-Sophie; Lancelot, Christine; Payen, Edmond (Journal of Molecular Catalysis A-Chemical, 2009)
Acetalization of glycerol with various aldehydes has been carried out using mesoporous MoO3/SiO2 as a solid acid catalyst. A series of MoO3/SiO2 catalysts with varying MoO3 loadings(1-20 mol%) were prepared by sol-gel technique using ethyl silicate-40 and ammonium heptamolybdate as silica and molybdenum source respectively. The sol-gel derived samples were calcined at 500 degrees C and characterized using various physicochemical characterization techniques. The XRD of the calcined samples showed the formation of amorphous phase up to 10 mol% MoO3 loading and at higher loading of crystalline alpha-MoO3 on amorphous silica support. TEM analyses of the materials showed the uniform distribution of MoO3 nanoparticles on amorphous silica support. Raman spectroscopy showed the formation of silicomolybdic acid at low Mo loading and a mixture of alpha-MoO3 and polymolybdate species at high Mo loadings. Moreover the Raman spectra of intermediate loading samples also suggest the presence of beta-MoO3. Acetalization of glycerol with benzaldehyde was carried out using series of MoO3/SiO2 catalysts with varying MoO3 loadings (1-20 mol%). Among the series, MoO3/SiO2 With 20 mol% MoO3 loadings was found to be the most active catalyst in acetalization under mild conditions. Maximum conversion of benzaldehyde (72%) was obtained in 8 h at 100 degrees C with 60% selectivity for the six-membered acetal using 20% MoO3/SiO2. Interestingly with substituted benzaldehydes under same reaction conditions the conversion of aldehydes decreased with increase in selectivity for six-membered acetals. These results indicate the potential of this catalyst for the acetalization of glycerol for an environmentally benign process. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Acetalization; Aldehyde; Glycerol; Silicomolybdic acid; solid acid

Deposition-precipitation versus anionic-exchange Au/Al2O3 catalysts: a comparative investigation towards the selective reduction of NOx - Nguyen, D. L.; Shubhangi B. Umbarkar; Dongare, Mohan K.; Lancelot, Christine; Girardon, J. S.; Dujardin, Christophe; Granger, P. (Catalysis Communications, 2012)
Catalytic properties of supported gold catalysts on gamma-Al2O3 prepared by a conventional deposition-precipitation method were compared with those obtained by anionic-exchange for the reduction of NOx by hydrocarbon under lean conditions that simulate Diesel engine exhaust gas. Interestingly, a catalytic activity enhancement is observed after thermal ageing under reactive conditions at 500 degrees C on anionic-exchanged samples which make them suitable for practical developments. On the other hand, the reverse trend is observed on the solids prepared by deposition-precipitation which deactivate at low temperature. Such changes in catalytic properties have been tentatively explained on the basis of textural and structural modifications taking place during thermal ageing under wet atmosphere. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Anionic-exchange; Au catalyst; Deposition-precipitation; NOx abatement; Selective catalytic reduction

One-pot sol-gel preparation for efficient cobalt-molybdenum-titania hydrotreating catalysts - Nguyen, D. L.; Gillot, S.; Souza, D. O.; Blanchard, P.; Lamonier, Carole; Berrier, E.; Kotbagi, T. V.; Dongare, Mohan K.; Shubhangi B. Umbarkar; Cristol, S.; Payen, E.; Lancelot, Christine (Chemcatchem, 2012)
Titania-based hydrodesulfurization catalysts were prepared by using a one-pot solgel method with the titanium peroxo complex as titanium precursor and molybdenum and cobalt precursors dissolved in the aqueous hydrogen peroxide solution used during synthesis. Catalysts with MoO3 loadings varying from 5 to 40 wt?% and a Co/Mo atomic ratio of 0.5 were prepared. Solids with molybdenum loadings below 20 wt?% MoO3 demonstrated poor hydrodesulfurization activity for the model compound thiophene. This was attributed to the presence of a large amount of embedded cobalt and molybdenum species in the titania matrix. A significant increase in the catalytic activity was observed for solids containing 20 and 25 wt?% of MoO3 on which active species appeared to be accessible on the titania surface. Furthermore, the highest conversion obtained on these solgel solids was superior to the highest conversion obtained on reference catalysts prepared through the impregnation of ammonium heptamolybdate and cobalt nitrate on commercial titania.
Keywords: cobalt; heterogeneous catalysis; Molybdenum; sol-gel process; titanium

Transesterification of diethyl oxalate with phenol over sol-gel MoO3/TiO2 catalysts - Kotbagi, Trupti; Duy Luan Nguyen; Lancelot, Christine; Lamonier, Carole; Thavornprasert, Kaew-Arpha; Zhu Wenli; Capron, Mickael; Jalowiecki-Duhamel, Louise; Shubhangi B. Umbarkar; Dongare, Mohan K.; Dumeignil, Franck (Chemsuschem, 2012)
The transesterification of diethyl oxalate (DEO) with phenol to form diphenyl oxalate (DPO) has been carried out in the liquid phase over very efficient MoO3/TiO2 solid-acid solgel catalysts. A selectivity of 100?% with a remarkable maximum yield of 88?% were obtained, which opens the route to downstream phosgene-free processes for the synthesis of polycarbonates. Interpretation of the results of various acidity measurements (NH3 and pyridine desorption, methanol oxidation as a probe reaction) allowed us to identify the catalytic sites as Lewis acid sites.
Keywords: heterogeneous catalysis; Lewis acids; Oxidation; sol-gel processes; transesterification

Promising stability of gold-based catalysts prepared by direct anionic exchange for DeNO (x) applications in lean burn conditions - Nguyen, D. -L.; Shubhangi B. Umbarkar; Dongare, Mohan K.; Lancelot, Christine; Girardon, J. S.; Dujardin, Christophe; Granger, P. (Topics in Catalysis, 2013)
Supported gold catalysts on gamma-Al2O3 have been investigated in the catalytic reduction of NO (x) in simulated Diesel exhaust gas conditions. Different parameters have been examined essentially the mode of gold incorporation via classical deposition-precipitation and anionic exchange methods and the nature of the pre-activation thermal treatment. The resistance to thermal ageing under reactive conditions at 500 A degrees C was found completely different with a significant rate enhancement on anionic-exchange samples. Further comparisons also show that the nature of the pre-activation thermal treatment influences the extent of surface reconstructions during thermal ageing with a detrimental effect of reductive pre-treatment on the catalytic performances.
9th International Congress on Catalysis and Automotive Pollution Control (CAPoC), Brussels, BELGIUM, AUG 29-31, 2012
Keywords: Anionic-exchange; Au/Al2O3 catalyst; Deposition-precipitation; NOx abatement; Selective catalytic reduction

Rational preparation of Ag and Au bimetallic catalysts for the hydrocarbon-SCR of NOx: sequential deposition vs. coprecipitation method - More, Pavan M.; Nguyen, D. L.; Dongare, Mohan K.; Shubhangi B. Umbarkar; Nuns, N.; Girardon, J. S.; Dujardin, Christophe; Lancelot, Christine; Mamede, Anne-Sophie; Granger, P. (Applied Catalysis B-Environmental, 2015)
This study emphasizes the importance of the preparation method for bimetallic Au-Ag catalysts supported on alumina in the selective reduction of NOx by hydrocarbons with gas feed compositions representative of diesel fuelled engine exhaust gas. An optimal balance between oxidative and reductive surface properties is obtained when Au and Ag are successively introduced. Significant re-dispersion processes take place when the catalyst runs at 500 degrees C leading to a gain in activity at low temperature and ascribed to a better interaction between Au and Ag species. Co-precipitation leads to a preferential formation of intermetallic Au-Ag particles which is detrimental to the catalytic performances. Aging at 500 degrees C leads to a significant particle sintering and a strengthening of the metallic character. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Au-Ag particles; Co-precipitation; DeNO(x) reaction; HC-SCR